Advancing Tyre and Road Wear Particle Measurements: Balancing Laboratory Conditions and Real-World Relevance - Jens Wahlström; Yezhe Lyu; Joacim Lundberg; Joakim Pagels; Rikard Hjelm (Atmosphere)
Non-exhaust emissions from the wear of brakes, tyres, and roads have become an increasing concern in recent years, already surpassing exhaust emissions by mass in many countries. However, there is a lack of studies in the scientific literature on test methods that include both real tyre and road materials. This is crucial for accurately replicating the tribological mechanisms and resulting emissions that occur during real-world driving. This study therefore employs a scaled experimental approach to investigate the influence of representative urban load and sliding speed conditions on tyre and road wear particle generation using commercial tyre and road materials. Friction, wear, and emissions were analysed using a pin-on-disc tribometer within a controlled environment, enabling the measurement of both airborne and non-airborne wear particles. The results demonstrate that under moderate test conditions, airborne tyre and road wear particle concentrations remained almost zero, with reasonable coefficients of friction and estimated non-airborne emission factors. However, under harsher contact conditions, the coefficients of friction, airborne tyre and road wear concentrations and estimated emission factors increased significantly, leading to excessive material detachment from both the tyre and road surface. These extreme wear conditions are not representative of real-world tyre–road interactions, emphasising the sensitivity and necessity of using more realistic test conditions in future studies.